2010
DOI: 10.1016/j.camwa.2009.08.015
|View full text |Cite
|
Sign up to set email alerts
|

Some uniqueness and existence results for the initial-boundary-value problems for the generalized time-fractional diffusion equation

Abstract: a b s t r a c tIn this paper, some uniqueness and existence results for the solutions of the initialboundary-value problems for the generalized time-fractional diffusion equation over an open bounded domain G × (0, T ), G ⊂ R n are given. To establish the uniqueness of the solution, a maximum principle for the generalized time-fractional diffusion equation is used. In turn, the maximum principle is based on an extremum principle for the CaputoDzherbashyan fractional derivative that is considered in the paper, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
145
0
5

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 254 publications
(151 citation statements)
references
References 11 publications
1
145
0
5
Order By: Relevance
“…The same author proved in [13] the existence of the solution using the notion of a generalized solution and the Fourier method of the variable separation. It should be noted that the generalized solution defined in [13] is a continuous function up to the boundary, not a generalized one.…”
Section: ) Is a Solution Of (Tfde) With The Condition (31) Providedmentioning
confidence: 99%
“…The same author proved in [13] the existence of the solution using the notion of a generalized solution and the Fourier method of the variable separation. It should be noted that the generalized solution defined in [13] is a continuous function up to the boundary, not a generalized one.…”
Section: ) Is a Solution Of (Tfde) With The Condition (31) Providedmentioning
confidence: 99%
“…For α = 2, the fractional Laplacian (−∆) α 2 is simply −∆, and thus Equation (1) is a particular case of the time-fractional diffusion-wave equation that was considered in many publications, including, for example, [1, 2,5,[14][15][16][17]. For α = 2 and β = 1, Equation (1) is reduced to the diffusion equation, and for α = 2 and β = 2, it is the wave equation that justifies its denotation as a fractional diffusion-wave equation.…”
Section: Problem Formulationmentioning
confidence: 99%
“…Now we proceed with the case x = 0 and first discuss the convergence of the integral in the integral representation given by Equation (16). It follows from the asymptotic formulas for the Mittag-Leffler function and the known asymptotic behavior of the Bessel function (see, e.g., [20]) that the integral in Equation (16) converges conditionally in the case n < 2α + 1 and absolutely in the case n < 2α − 1.…”
Section: Mellin-barnes Representations Of the Fundamental Solutionmentioning
confidence: 99%
“…Some partial dierential equations of fractional order type like one-dimensional time-fractional diusion-wave equation were used for modeling relevant physical processes (see [26]). Regarding fractional partial dierential equations, Luchko [18] used the Fourier transform method of the variable separation to construct a formal solution and under certain condition he showed that the formal solution is the generalized solution of the initial-boundary value problem. To prove the uniqueness he used the maximum principle for generalized time fractional diusion equation [17].…”
Section: Introductionmentioning
confidence: 99%